Learning Management by Using Critical Inquiry Methods Integrated with Cooperative Learning to Develop Criminology Literacy for Pre-Service Social Studies Teachers - Khanitcharongkul, Auttapol (Rajapark Journal, 2024)
This research aimed to 1) develop learning activities using inquiry-based learning integrated with cooperative learning for pre-service Social Studies teachers, 2) study the effects, and 3) examine the students’ satisfaction. This quantitative research involved a target group consisting of 30 fourth-year students from the Social Studies Teaching Program at the School of Education, University of Phayao, during the academic year 2024. The target group was selected using purposive sampling. The research tools included 1) five lesson plans totaling 15 hours, 2) a 50-item criminology literacy test, and 3) a student satisfaction questionnaire regarding the learning arrangement. Data analysis employed descriptive statistics, including mean, standard deviation, and t-test statistics. The research findings revealed that 1) the developed lesson plans consisted of five plans, each comprising five steps, which are: Step 1: Explore Data; Step 2: Analyze Data; Step 3: Compile Knowledge; Step 4: Check Knowledge; and Step 5: Summary of Knowledge. 2) The students’ post-learning criminology literacy scores were significantly higher than their pre-learning scores at the.05 level, and 3) the students’ satisfaction with the learning arrangement was at a high level.